2013
DOI: 10.1111/rode.12038
|View full text |Cite
|
Sign up to set email alerts
|

Business Cycle Synchronization between Euro Area andCentral andEasternEuropeanCountries

Abstract: We analyze the degree of co‐movements in real macroeconomic aggregates across selected euro area and Central and Eastern European (CEE) countries applying a multi‐factor model. Our results suggest that the evolution of the global European factor matches well the narrative of main economic events between 1995 and 2011, capturing among others the recession during the recent global financial and economic crisis. This factor plays a central role in explaining real output growth variability in euro area and is negl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…With respect to Hungary and the Czech Republic, their business cycles co-move with the EU-12 after 2005. Jiménez- Rodríguez et al (2013) also find high correlations of CEE countries (except for the Czech Republic) with the EU business cycle. However, contrary to this result, they find that these countries exhibit a lower level of concordance when a factor model is employed.…”
mentioning
confidence: 84%
“…With respect to Hungary and the Czech Republic, their business cycles co-move with the EU-12 after 2005. Jiménez- Rodríguez et al (2013) also find high correlations of CEE countries (except for the Czech Republic) with the EU business cycle. However, contrary to this result, they find that these countries exhibit a lower level of concordance when a factor model is employed.…”
mentioning
confidence: 84%
“…They suggested that some countries like Slovakia and Slovenia—already EA members—react more strongly to foreign industrial production shocks than other countries. In another study (Jimenez‐Rodríguez, Morales‐Zumaquero, & Egert, ), these authors found the same result: Slovakia and Slovenia exhibit a high degree of concordance with the European business cycle. The degree of concordance is similar to that of the Netherlands or Spain.…”
Section: Literature Reviewmentioning
confidence: 59%
“…Paper Methodology Artis and Zhang (1997) Correlations between the cyclical series across countries Fratzscher (2002) Tri-variate VAR-GARCH(1,1) Kalemli-Ozcan et al (2001) Correlation and utility-based measure of fluctuations asymmetry Doyle and Faust (2002) Correlation Hallett and Piscitelli (2002) IMFs Multimod Econometric Model Imbs (2004) Estimation of a system of simultaneous equation Kalemli-Ozcan et al (2003) Constant Relative Risk Aversion Utility Kose et al (2003) Simple correlation and dynamic unobserved factor model Micco et al (2003) Gravity model of trade Artis et al (2004) Markov Switching Model Nitsch (2004) Multivariate Logit Model Doyle and Faust (2005) Rolling correlations Mann-Quirici (2005) Vector Autoregressive Model Lane and Walti (2006) Correlation Alesina et al (2008) GLS regression Kose et al (2003b) Bayesian dynamic latent factor model Kenourgios et al (2009) Asymmetric Generalized Dynamic Conditional Correlation Park and Shin (2009) Cyclical measure of output for the three blocs Walit (2009) Concordance measure Fidrmuc and Korhonen (2010) Dynamic correlations Caporale and Spagnolo (2011) Tri-variate VAR-GARCH(1,1) He and Liao (2011) Multi-level structural factor model Kim et al (2011) Panel VAR Willett et al (2011) Correlations of GDP growth and deviation from GDP growth trend Jimenez- Rodriguez et al (2013) Markov Switching Model and concordance indices…”
Section: Appendix Table A1 Papers Using a Variety Of Methodologiesmentioning
confidence: 99%